ANALISIS GAYA BAHASA SINDIRAN DALAM KANAL YOUTUBE DEDDY CORBUZIER EPISODE SOMASI TAHUN 2023 - Aldo Lauren Wijaya; Eti Sunarsih; Gunta Wirawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the satire language style in Deddy Corbuzier's YouTube channel in 2023, as well as the implementation of research results in class X Indonesian language lesson plans. The method used in this research is qualitative method with descriptive form. The data source of this research is the subpoena video in Deddy Corbuzier's YouTube channel in 2023, and the data of this research is in the form of speech related to the sarcasm language style in the subpoena video in Deddy Corbuzier's YouTube channel in 2023. The data collection technique in this research uses documentary study techniques. This research is analyzed using Gorys Keraf's theory, which focuses on speech related to irony, cynicism, sarcasm, satire, inuendo, antiphrasis, and paronomasia. The results of this study found 67 data included in the satire language style, the data obtained include irony 5 data, cynicism 21 data, sarcasm 15 data, satire 18 data, inuendo 2 data, antiphrasis no data found, and paronomasia 6 data. The results of this study are planned to be implemented in the teaching module of the independent curriculum on learning materials related to satirical language styles in the YouTube application in class X material for Senior High School (SMA), namely in Chapter 2: Expressing Criticism Through Smiles. Language learning materials in class X SMA Indonesian lessons, contained in the Learning Outcomes (CP) and Learning Flows and Objectives (ATP) which are included in the phase E category. In more detail, namely in the CP Reading and Viewing Elements in phase E with learning objectives: 2.1 Learners are able to listen to aural anecdote text in order to evaluate the ideas and messages conveyed in the monologue text of a single joke critically and reflectively and 2.3 Learners are able to use the language rules used in conveying social criticism.